Haff disease - are we threatened with another epidemic? - Przemysław Paul; Katarzyna Kanclerz; Alicja Kubanek; Andrzej Bałasz; Marcin Renke (Nofer Institute of Occupational Medicine, 2021)
Haff disease is a group of symptoms caused by rhabdomyolysis following ingestion of some species of fish and crayfish. Pathophysiology remains unknown. Outbreaks of the Haff disease have been reported in many regions of the world. In this article we present the case of a 38-years-old patient, professional fisherman, suspected of suffering from Haff disease. He developed symptoms of diffuse myalgia, headache, chest pressure, brown-colored urine and elevated blood pressure. Predominant laboratory abnormalities were elevated serum creatine kinase and creatinine concentrations. During hospitalization the patient required the renal replacement therapy. As a result of applied procedures, clinical and laboratory improvement was achieved. The patient was discharged home in good general condition. The Haff disease should be included in the differential diagnosis of rhabdomyolysis. Detailed medical interview, especially questions about recently consumed food and occupational exposure, is crucial in making a proper diagnosis. Med Pr. 2021;72(5):605-10